Respuesta :
Answer and Step-by-step explanation:
We want to verify that (1 + cos(2θ)) / 2cos(θ) = cos(θ).
Let's focus on the left side. Look at cos(2θ). This is an identity, so remember that cos(2θ) = cos²θ - sin²θ. Also, look at the 1. Remember that sin²θ + cos²θ = 1, so plug both of these expressions into our equation:
(1 + cos(2θ)) / 2cos(θ) =? cos(θ)
((sin²θ + cos²θ) + (cos²θ - sin²θ)) / 2cos(θ) =? cos(θ)
2cos²θ / 2cosθ =? cosθ
cosθ = cosθ
Thus, we have proved this is an identity.
Answer:
(1 + cos(2theta))/2cos(theta)
cos(2theta) = 2cos²(theta) - 1
(1 + 2cos²(theta) - 1)/2cos(thetal
2cos²(theta)/2cos(theta)
cos(theta)